Protest Against The Domination Of Tribal Customs In Nujood Ali's And Delphine Minuoi's I Am Nujood, Age 10 And Divorced Memoir (2010): A Critical Discourse Analysis - Maryati, Tri (2012)
The major problem of this study is to reveal the dominant ideology reflected in the Njood Ali''s and Delphine Minuoi's I am Nujood, Age 10 and Divorced Memoir . The objectives of the study are; to analyse the structural elements of the memoir and to reveal the dominant ideology reflected in the memoir by using Critical Discorse Analysis approach. In conducting the study, the researcher uses qualitative research in which the data are based on primary data source, the memoir of Nujood Ali's and Delphine Minuoi's I am Nujood, Age 10 and Divorced. The secondary data are other data such as, biography of the author, some books related to the study, and website from the internet. In analysing the data, she applies two analysis, firtsly, structural approach of CDA which is used to analyze the elements of the memoir. It consists of Macrostructure, Superstructure, and Microstructure. Secondly, the writer discussed the social cognition of the memoir which due to the historical background of the memoir and the writer. The finding of the research shows as follows: firstly, based in the structural analysis, it is evident that in I am Nujood, Age 10 and Divorced, Minuoi protests against the domination of tribal customs as western toward patriarchal culture. Secondly, based on the social cognition analysis, it is apparent that the values underlying the part, includes human freedom, marriage, women's right, women's role, responsibility, and childcare. The values imply that the dominant ideology is liberal feminism.